Entropy Generation Analysis for the Peristaltic Motion of Ree-Eyring Fluid through a Porous Symmetric Channel under Slip Constraints - Zaheer Abbas; Muhammad Yousuf Rafiq; Salita Yaqoob; Shahzad, Hafiz (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2025)
Peristaltic-driven flows play a critical role in many natural biological processes and have inspired numerous applications in engineering, medicine, and environmental technology. By mimicking the efficient movement and control of peristaltic, scientists and engineers can develop innovative solutions for a wide range of challenges. Therefore, this article delves into the peristaltic flow of electrically conducting Ree-Eyring fluid in a non-uniform symmetric conduit with entropy generation. Slip constraints and radiative impacts are also deliberated. The lubrication theory hypothesis is utilized to compress the normalized equations. Closed-form outcomes are derived and exhibited graphically to depict the distributions of velocity, entropy generation, temperature, and pressure optimization. The outcomes of this investigation showed that the liquid velocity is demoted by improving the Ree-Eyring and slip parameters. Further, the liquid temperature is boosted by augmenting the values of the Ree-Eyring fluid parameter and Brinkman number.